(A)tonality in the Compositional Language of Peter Klatzow: A Triadic Study with an Added Note. Issue 1 (2nd January 2017) - Delport, Wilhelm
ABSTRACT: This article adopts a triadic study to the exploration of (a)tonality in Peter Klatzow's compositional language. Firstly, academic scholarship on tonality, modality and atonality in the composer's oeuvre is summarised from a literary perspective. This is followed by an analysis of a more recent work, Sur une route toute blanche, dans un immense paysage (2010). An interview with Klatzow on questions concerning tonality constitutes the final section. It is concluded that the tonal practices of Klatzow's youth were replaced by avant-garde experimentation and atonal writing in the mid-1960s. The composer developed a unique voice in the late 1970s, characterised by the use of small intervallic cells, and the juxtaposition of tonal and atonal elements. A rapprochement of tonality in Klatzow's compositional language has been evident since the late 1980s, with a preference for modal and octatonic material, and without the complete abandonment of atonal practices. The compositional language of Sur une route toute blanche, dans un immense paysage can be considered neo-tonal in many respects. Consonant triads embellished with added notes are placed within non-functional, quasi-tonal frameworks. The compositional process is regulated by linearly combined pitch collections, while pedal notes, ostinatos and pitch emphases create a sense of tonal centrality. Klatzow believes that conventional tonal and modal practices are modified and extended into greater tonal complexes in his writing.